ANALISIS PEMBELAJARAN BERBASIS INKUIRI PADA PEMBELAJARAN IPA TERHADAP KETERAMPILAN BERPIKIR KRITIS SISWA SDS PELANGI - Rose D.O. Tambunan; Nurhairani; Irsan; Nurmayani; Imelda Free Unita Manurung (STKIP Subang, 2026)
This study aimed to analyze inquiry-based learning in science instruction toward students' critical thinking skills at SDS Pelangi. This study employed a qualitative approach with a case study design. The research subjects consisted of two fifth-grade teachers as key informants, ten fifth-grade students, and one principal as supporting informants. Data were collected through interviews, observations, and documentation and analyzed using the interactive model of Miles and Huberman, including data collection, data condensation, data display, and conclusion drawing/verification. The findings revealed that teachers understood inquiry-based learning as a learning process that actively involved students in discovering concepts through observation and experimental activities. The implementation of inquiry-based learning encouraged students to participate in observation, investigation, discussion, and conclusion drawing during science learning. Students' critical thinking skills were reflected in the indicators of interpretation, analysis, inference, evaluation, explanation, and self-regulation, which developed through meaningful learning experiences.